Image encryption : a communication perspective /: a communication perspective. ([2014]) - Abd el-Samie, Fathi E; Ahmed, Hossam Eldin H; Elashry, Ibrahim F; Shahieen, Mai H; Faragallah, Osama S; El-Rabaie, El-Sayed M; Alshebeili, Saleh A
No abstract available